Blunted HPA axis activity prior to suicide attempt and increased inflammation in attempters. (March 2017) - Melhem, Nadine M.; Munroe, Sara; Marsland, Anna; Gray, Katarina; Brent, David; Porta, Giovanna; Douaihy, Antoine; Laudenslager, Mark L.; DePietro, Frank; Diler, Rasim; Driscoll, Henry; Gopalan, Priya
Highlights: This is the first study to show low hair cortisol concentrations in attempters. In our study, hair cortisol concentrations reflect levels prior to suicide attempt. Attempters also show low GR-α mRNA and increased C-reactive Protein and TNF-α mRNA. This is a distinct biological profile compared to ideators and healthy controls. Hair cortisol was associated with GR-α mRNA, childhood abuse, and perceived stress Abstract: Background: Hypothalamic-Pituitary-Adrenal (HPA) axis dysregulation is associated with increased risk for suicidal behavior. However, it is not clear whether such dysregulation exists prior to or is a consequence of attempt. Studies also show an activation of inflammatory responses in suicidal behavior but often combine attempters with those with ideation. Methods: The sample consisted of psychiatric inpatients, aged 15–30 years, admitted for suicide attempt (SA, n = 38), inpatients admitted for suicidal ideation with no prior history of attempts (SI, n = 40), and healthy controls (n = 37). We compared SA, SI, and controls on hair cortisol concentrations (HCC), which provides retrospective levels of cortisol and thus prior to the attempt in SA. We also compared them on the expression of genes in the HPA axis and inflammatory pathways previously implicated in suicidal behavior (GR or NR3C1, SKA2, FKBP5, IL-1β, TNF-α ); plasma C-Reactive Protein (CRP); and cellular measures of glucocorticoid receptor (GR) sensitivity and stimulated production of IL-6. Results: We found lower HCC [β = −0.55, 95% CI (−0.96, −0.13), p = 0.01, ES = −0.54] in first-time SA compared to SI and controls. In addition, SA showed lower GR or NR3C1 (α isoform) mRNA [β = −5.11, 95% CI (−10.9, 0.73), p = 0.09, ES = −0.46], higher CRP [β = 0.94, 95% CI (−0.004, 1.9), p = 0.05, ES = 0.60], and higher TNF-α mRNA [β = 26.4, 95% CI (7.7, 45.2), p = 0.006, ES = 0.73]. Conclusions: This is the first study to differentiate youth who attempt suicide from those with suicidal ideation on HCC and to show that low HCC precedes suicide attempt. Suicide attempters also showed a distinct biological profile on several markers in both the HPA axis and inflammatory pathways. Future longitudinal studies are needed to examine the ability of these biomarkers to predict suicidal behavior.